Application of Patient Safety Targets in Hospital: A Literature Review - Nela Rosa; Siti Saidah Nasution (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Patient safety is the basic value of service to avoid undesirable incidents for patients. Patient safety targets as a strategy to reduce the risk of near misses, and undesirable or unexpected events. One of the hospital's obligations is to improve the quality of hospital services, including patient safety. The purpose of this study was to identify patient safety targets in hospitals. The study design used was a literature review using keywords based on a database of research articles, such as Scopus, ScienceDirect, PubMed, Google Scholar, and Garuda from 2012 to 2022. There were 1408 articles with ten relevant articles for review and analysis. Knowledge, attitudes, competencies, awareness, and culture are important to build the application of patient safety so that a good organizational system, nursing care, and teamwork will increase and the quality of service will be improved in the hospital. Abstrak: Keselamatan pasien merupakan nilai dasar pelayanan untuk menghindari kejadian yang tidak diinginkan kepada pasien. Target keselamatan pasien sebagai strategi untuk mengurangi risiko kejadian nyaris celaka, kejadian yang tidak diinginkan atau tidak diharapkan. Salah satu kewajiban rumah sakit adalah meningkatkan mutu pelayanan rumah sakit, termasuk keselamatan pasien. Tujuan dari penelitian ini adalah untuk mengidentifikasi target keselamatan pasien di rumah sakit. Desain penelitian yang digunakan adalah literature review dengan menggunakan kata kunci berdasarkan database artikel penelitian, seperti Scopus, ScienceDirect, PubMed, Google Scholar, dan Garuda dari tahun 2012 hingga 2022. Terdapat 1408 artikel dengan 10 artikel yang relevan untuk direview dan dianalisis. Pengetahuan, sikap, kompetensi, kesadaran, dan budaya penting untuk membangun penerapan keselamatan pasien sehingga sistem organisasi, asuhan keperawatan, dan kerjasama tim yang baik akan meningkat dan juga kualitas pelayanan di rumah sakit akan meningkat.